Octopus engineering, intentional and inadvertent. Issue 1 (2nd January 2018) - Scheel, David; Godfrey-Smith, P.; Linquist, S.; Chancellor, S.; Hing, M.; Lawrence, M.
ABSTRACT: We previously published a description of discovery of a site where octopuses live in an unusually dense collection of individual dens near one another in a bed of scallop shells amid a rock outcrop. We believe the shell bed is an extended midden, accumulated over time by individual octopuses returning to their dens with food. Here we consider what aspects of material collection, den maintenance, and aggregation are intentional for the octopuses, versus inadvertent consequences of individual decisions. Collection of prey items, transport of prey to the den, den excavation, and collection and use of non-prey materials at the den appear to be intentional behaviors. The occurrence of many dens in close aggregation appears to be an inadvertent outcome of the availability of food and the risk of predation in the habitat. Popular media reports have described this site as an 'city' designed by octopuses, but that is not an accurate description of the site.